2012
DOI: 10.1038/srep00339
|View full text |Cite
|
Sign up to set email alerts
|

Strong Superconducting Proximity Effect in Pb-Bi2Te3 Hybrid Structures

Abstract: To study the interface between a conventional superconductor and a topological insulator, we fabricated Pb-Bi2Te3-Pb lateral and sandwiched junctions, and performed electron transport measurements down to low temperatures. The results show that there is a strong superconducting proximity effect between Bi2Te3 and Pb, as that a supercurrent can be established along the thickness direction of the Bi2Te3 flakes (100~300 nm thick) at a temperature very close to the superconducting Tc of Pb. Moreover, a Josephson c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
164
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(174 citation statements)
references
References 21 publications
10
164
0
Order By: Relevance
“…[19][20][21][22][23]. Gate tunable supercurrent has been observed and argued to be due to the TI surface state [19].…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…[19][20][21][22][23]. Gate tunable supercurrent has been observed and argued to be due to the TI surface state [19].…”
mentioning
confidence: 88%
“…Gate tunable supercurrent has been observed and argued to be due to the TI surface state [19]. Superconducting quantum interference devices based on such junctions have also been demonstrated [22,24]. Thus the flat Andreev bound states at zero energy, and the zero bias conductance peak in the local density of states, predicted here should be experimentally accessible.…”
mentioning
confidence: 95%
“…6) It is useful to note that such a proximity-induced superconducting state on the surface of a TI has singlet Cooper pairs, but nonetheless it is topologically nontrivial due to the Berry phase born by the surface Dirac electrons; therefore, such a surface can be considered a 2D topological superconductor. There have been a number of experimental reports to confirm the superconducting proximity effect in the topological surface states, 171,231,[260][261][262][263][264][265][266][267][268] but the existence of Majorana fermions has not been elucidated.…”
Section: Majorana Fermionsmentioning
confidence: 99%
“…Recently, Koren et al observed that the superconductivity below 2-3 K in Bi 2 Se 3 and Bi 2 Te 2 Se films, which was attributed to proximity-induced local superconductivity by small amounts of superconducting Bi inclusions or segregation to the surface with T c of 6.3 K. 24 Furthermore, the strong superconducting proximity effect in Pb-Bi 2 Te 3 -Pb hybrid structures was also reported, 22 in which a supercurrent can be established through 100-300-nm-thick Bi 2 Te 3 flakes at a temperature of ∼7.2 K. Also, it has been observed that PE-induced superconducting state in Bi 2 Se 3 exists over an extended distance of ∼1 μm away from the Pb-Bi 2 Se 3 interface. 21 In regard to this mechanism, the induced superconducting regions [(adjacent to the Bi clusters/Bi 2 Te-3 interfaces, orange regions in Fig.…”
mentioning
confidence: 99%